2022
DOI: 10.3389/fphar.2022.822193
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Analysis Coupled With UPLC/MS on Therapeutic Effect of Jigucao Capsule Against Dampness-Heat Jaundice Syndrome

Abstract: Dampness-heat Jaundice Syndrome (DHJS) is a complex Chinese medicine syndrome, while Jigucao capsule (JGCC) is an effective compound preparation of Chinese medicine for the treatment of DHJS about liver and gallbladder, but its mechanism is not clear yet. The purpose of this study is to clarify the pathogenesis of DHJS and the treatment mechanism of JGCC. We used ultra-high performance liquid chromatography/mass spectrometry (UPLC/MS) combined with pattern recognition, accompanied the advanced software and onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The source of the serum samples was based on the samples of our previous metabolomics study on JGCC in the treatment of DHJS [ 6 , 7 ]. Eight-week-old clean-grade adult male SD rats were purchased from Guangxi Medical University (license number SYXK (Gui) 2020-0014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The source of the serum samples was based on the samples of our previous metabolomics study on JGCC in the treatment of DHJS [ 6 , 7 ]. Eight-week-old clean-grade adult male SD rats were purchased from Guangxi Medical University (license number SYXK (Gui) 2020-0014).…”
Section: Methodsmentioning
confidence: 99%
“…It mainly presents with three yellow symptoms, including yellow eyes, yellow body and yellow urine, as well as pathological manifestations such as thirst and fever, inappetence, disgusting vomits and poor defecation [ 5 ]. Metabolomics studies have shown that JGCC has a significant therapeutic effect on rats with DHJS by acting on some abnormal metabolic pathways such as pentose and glucuronate interconversions, arachidonic acid metabolism and primary bile acid biosynthesis [ 6 , 7 ]. On the other hand, modern pharmacological studies have shown that JGCC combined with entecavir antiviral treatment of patients with chronic hepatitis B can enhance its antiviral effects and delay the progression of liver fibrosis by reducing serum transforming growth factor-β1, transaminase, total serum bilirubin and other liver function indicators [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al (2020) used UPLC-Q-TOT-MS to quantitatively analyze the multiple biotransformation products of Xian-Ling-Gu-Bao (XLGB) with rat intestinal bacteria, and this study method successfully described the dynamic contour of thirtyone biotransformation substances of XLGB. He et al (2022) studied the role of Jigucao capsule (JGCC) in the treatment of Dampnessheat Jaundice syndrome (DHJS) using a classical strategy, which is a research technique of UPLC-QTOF-MS united with pattern identification along with metabolomics applications and digital databases JGCC has been found to call back twenty-five potential biomarkers, including arachidonic acid, L-urobilin, etc. Yao et al (2022) used UPLC-QTOF-MS to find that Longzuantongbi granules effectively regulated 11 biomarkers associated with lipid metabolism and amino acid metabolism, such as lysophosphatidylcholine, alpha-3-hydroxybutyric acid, alpha-linolenic acid, arachidonic acid, and 12-HETE.…”
Section: Pharmacodynamic Evaluationmentioning
confidence: 99%
“…In the reported references, many studies have focused on the application of analytical techniques to the quantification of target compounds in Abri Herba and/or Abri mollis Herba, 1,[12][13][14] and explored the mechanism of JGCC. 3,15 In the best of our knowledge, there was only one report focused on the characterization of multiple target compounds in JGCC. 16 Therefore, it is required to develop a suitable method for the quantitative analysis of multiple components in these medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, many methods have been developed to analyse the multiple components in complex drugs, such as fourier transform infrared spectroscopy (FTIR), 4 raman spectroscopy, 5 nuclear magnetic resonance (NMR), 6 capillary electrophoresis (CE), 7 electrochemical sensors, 8 high performance liquid chromatography (HPLC), 9 liquid chromatography‐mass spectroscopy (LC–MS), 10 supercritical fluid chromatography (SFC) 11 and so on. In the reported references, many studies have focused on the application of analytical techniques to the quantification of target compounds in Abri Herba and/or Abri mollis Herba, 1,12–14 and explored the mechanism of JGCC 3,15 . In the best of our knowledge, there was only one report focused on the characterization of multiple target compounds in JGCC 16 .…”
Section: Introductionmentioning
confidence: 99%